Pendidikan Madrasah Sebagai Sub-Sistem Pendidikan Nasional - Adi Kasman (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2018)
Historically education in the form of madrasah can not be isolated in the history of the nation of Indonesia, education in madrasah is the core key, the only educational institution that has long been growing and developing in Indonesia before the Dutch colonial government came and introduced the school system on the 19th abd. The colonial presence of the colonials made the education system into a duality of its style, where Islamic education at the madrasah at that time continues to run in order to expand and deepen the science of education about the Islamization for Indonesian nationals who are Muslims and on the other side of the school built by the colonial government also continues to run . Both run in very different conditions both in the provision of learning materials and in terms of performance.